A comparison of full-field digital mammograms versus 2D synthesized mammograms for detection of microcalcifications on screening. Issue 107 (October 2018) - Wahab, Rifat A.; Lee, Su-Ju; Zhang, Bin; Sobel, Lawrence; Mahoney, Mary C.
Highlights: With synthetic 2d imaging, there is a reduction in 40-50% of the radiation dose by eliminating the full field digital mammogram. Radiologists should be aware image artifacts present on synthetic 2D images when evaluating potential microcalcifications. Our study demonstrates that FFDM and synthetic 2D mammograms have acceptable observer agreement for detection of microcalcifications at screening. Abstract: Objectives: To compare the observer agreement of microcalcification detection on synthetic 2D images to full field digital mammography (FFDM) at screening and determine if calcifications can be detected to the same degree and given the same BI-RADS assessment. Material and methods: Two-experienced radiologists retrospectively reviewed synthetic 2D images and FFDM, in separate sessions, to detect microcalcifications and provide a BIRADS assessment. A third experienced breast radiologist reviewed the cases that were disagreed upon and gave a final assessment. Between March 2016–December 2016, 414 women obtained a screening mammogram with tomosynthesis and acquisition of FFDM. 71 cases had combined FFDM and tomosynthesis images, calcifications visible on FFDM or no calcifications present, which comprised the study group. Synthetic 2D images were constructed from the DBT images. During session 1, all synthetic 2D images for the 71 cases were reviewed. During session 2, all the FFDM images for the 71 cases were reviewed. Tomosynthesis images were not reviewed. The agreement of detection of calcifications and BIRADS assessment between radiologists for FFDM and synthetic 2D images were assessed using Cohen's kappa test. Fisher's exact test was used to detect the differences in calcification identification among various breast densities on FFDM and synthetic 2D images. Results: For the detection of calcifications between synthetic 2D images and FFDM, there was moderate to substantial agreement (p-values < 0.0001) for the two radiologist. For the BIRADS assessments, the agreement between synthetic 2D imaging and FFDM was moderate (p-values < 0.0001). The inter-reader agreement for detection of calcifications was fair for using synthetic 2D and moderate for using FFDM (p-value < 0.0001). The final inter-reader agreement between FFDM and synthetic 2D images for the detection of calcifications was moderate (p-values < 0.0001) with the addition of the third reader. For the final BI-RADS assessment, there was moderate agreement between synthetic 2D imaging and FFDM (p-value < 0.0001). The two readers did not demonstrate a significant difference in the detection of microcalcifications for those who were dense or non-dense (p-value range 0.076–0.302). Conclusion: Radiologist interpreting synthetic 2D imaging and FFDM have similar frequency for detection of calcifications and BIRADS assessment. A synthetic 2D mammogram may be a sufficient replacement for FFDM at screening.